Study on Shaping and CO2/N2 Separation Performance of Porous Material M-MOF-74(M=Mg, Co, Ni) - Xiaohua LIU; Yang CHEN; Jinlong LI; Chunyu LU; Yi WANG; Libo LI; Jinping LI (Taiyuan Ligong Daxue xuebao, 2022)
M-MOF-74 (M=Co,Mg,Ni) material has excellent performance in CO2 capture, but the direct application of powdered MOF-74 material in practical industry will inevitably lead to problems such as heat/mass loss, fluid pressure drop, pipeline blockage, recovery difficulty and so on. In order to meet the requirements of “Double Carbon” goal and achieve efficient CO2 capture, a composite binder shaping process was developed. M-MOF-74 (M=Mg,Co,Ni) material was processed into spherical particles about 3 mm in size, and the mechanical strength, thermal stability, and CO2/N2 adsorption and separation performance of the granulated particles were tested. The results show that the mechanical strength of the shaped particles is 23~26 N, which can meet the industrial service life standard and has good thermal stability; the CO2 adsorption performance of the granulated particles decreases by less than 10%. The dynamic separation experiment of CO2/N2(15/85, volume ratio) mixture proved the excellent separation effect of the three granulated particles. The performance of these spherical adsorbents meets the standards of gas separation industry and can further reduce the energy consumption and operation cost in the process of CO2 capture. It is believed that this shaping method will greatly accelerate the commercialization of MOF.